Advancing Sustainable Energy Transition Through Green Hydrogen Valleys - Aymen Flah (22497344) (2025)
The development of Green Hydrogen Valleys (GHVs) is pivotal in the global shift toward sustainable energy and climate change mitigation. However, GHVs face challenges such as safe hydrogen injection, scalable electrolyzer deployment, and effective liquid hydrogen (LH2) containment, necessitating innovative solutions. This review offers a comprehensive analysis of current scientific literature and recent advancements in GHV implementation, focusing on critical areas including electrolysis technology, material compatibility, hydrogen transportation, and economic feasibility. It underscores the necessity of establishing a clean hydrogen value chain to achieve climate neutrality objectives. Additionally, the study outlines a three-phase roadmap—activation, scaling, and market integration—to facilitate the seamless incorporation of GHVs into the energy sector. Through this analysis, the review provides valuable insights for researchers, industry stakeholders, and policymakers, guiding strategic decisions and investments toward a sustainable energy future powered by green hydrogen. The findings underscore the significant role of GHVs in achieving climate and sustainability goals by reducing emissions and meeting global energy demands. Notably, scaling green hydrogen production could reduce carbon dioxide emissions of global energy demands by 2050. This review emphasizes the importance of international collaboration and ongoing research efforts to expedite GHV deployment and maximize their climate benefits. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2025.3542554